The Influence of Promotion, Product Quality, and Service Quality on Fixed Broadband Internet Consumer Satisfaction - Syeis, Muhammad; Helmi, Sulaiman; Gunarto, Muji (Yayasan Sembilan Pemuda Indonesia, 2024)
PT Eka Mas Republik is a company engaged in the field of Fixed Broadband internet service providers which aims to provide internet services to the community. This study aims to empirically determine the acceptance of Fixed Broadband PT Eka Mas Republik on the customer side. This study uses a model adopted from the variables of Media Promotion, Product Quality, Service Quality, and Customer Satisfaction. Furthermore, the model was analyzed using the Partial Least Square Structural Equation Model (SEM-PLS). The results showed varying relationships between exogenous variables and endogenous variables. First, the service quality variable has a significant effect on the consumer satisfaction variable. Second, the product quality variable has a significant effect on the consumer satisfaction variable, Third, the MP variable is proven to be significant to the service quality variable. Fourth, the product quality variable is proven to be significant to the service quality variable. Fifth, the MP variable does not prove significant to the consumer satisfaction variable. Sixth, the MP X service quality variable does not prove significant to the consumer satisfaction variable. Seventh, the product quality x service quality variable does not prove significant to the consumer satisfaction variable.